Tourism Sector and Regional Original Income in North Lombok (2015-2024): An Econometric Projection Analysis - Suprapto, Dedi; Fadliyanti, Luluk; Jumaedi, Jumaedi (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2025)
This study analyzes the impact of the tourism sector on Regional Original Revenue in North Lombok Regency and projects its growth trend until 2030. By using a quantitative descriptive approach, time series data from 2015 to 2024, analyzed with EViews 12. The results indicate that the number of tourist attractions, tourist arrivals, and tourism workforce have a positive and significant effect on Regional Original Revenue, while the number of restaurants and accommodation has a negative and significant effect. The estimated model demonstrates strong explanatory, with R² value 0.951039. Furthermore, the projection analysis shows a consistent upward trend, with Regional Original Revenue from tourism sector expected to reach Rp 465.44 billion by 2030. The findings highlight the importance of strengthening tourist attractions, increasing number of visitors, and enhancing the capacity of the tourism workforce in promoting sustainable economic growth. The study provides empirical evidence to support regional policymakers in optimizing tourism development strategies to enhance Regional Original Revenue and regional development planning.